2004
DOI: 10.1063/1.1753083
|View full text |Cite
|
Sign up to set email alerts
|

Stoner–Wohlfarth model applied to bicrystal magnetoresistance hysteresis

Abstract: We calculate numerically the magnetization direction as function of magnetic field in the StonerWohlfart theory and are able to reproduce the shape of the low-field magnetoresistance hysteresis observed in manganite grain boundary junctions. Moreover, we show that it is necessary to include biaxial magnetocrystalline anisotropy to fully describe the grain boundary magnetoresistance in La0.7Sr0.3MnO3/SrTiO3 bicrystal tunnel junctions.Can the fairly simple model presented by Stoner and Wohlfart in 1948 [1] pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…25. Figures 5͑e͒-5͑g͒ show how the magnetoresistance hysteresis varies with misorientation angle, as obtained from simulations using our model 25 for the present geometry. Each simulation starts from the saturated state in one field direction, and then the direction of magnetization is traced for decreasing fields through zero to saturation in the opposite field direction.…”
Section: A Magnetization Reversal In a Field Perpendicular To The Bimentioning
confidence: 90%
See 2 more Smart Citations
“…25. Figures 5͑e͒-5͑g͒ show how the magnetoresistance hysteresis varies with misorientation angle, as obtained from simulations using our model 25 for the present geometry. Each simulation starts from the saturated state in one field direction, and then the direction of magnetization is traced for decreasing fields through zero to saturation in the opposite field direction.…”
Section: A Magnetization Reversal In a Field Perpendicular To The Bimentioning
confidence: 90%
“…Details of the model can be found in Ref. 25. Figures 5͑e͒-5͑g͒ show how the magnetoresistance hysteresis varies with misorientation angle, as obtained from simulations using our model 25 for the present geometry.…”
Section: A Magnetization Reversal In a Field Perpendicular To The Bimentioning
confidence: 94%
See 1 more Smart Citation
“…We have previously shown that with the field along the strip line ðB ? GBÞ the magnetoresistance hysteresis can be analyzed within the Stoner -Wohlfarth model for reversal by coherent rotation of magnetization [3]. A typical result from simulations of the bicrystal magnetoresistance is shown in the inset of Fig.…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…The inset shows a simulated hysteresis using the Stoner-Wohlfarth model with the angles a ¼ 60 and b ¼ 90 as described in Ref. [3]. electrodes behave as single domains, and that the magnetization reversal process is determined by the coherent rotation of the direction of magnetization in each of the electrodes.…”
Section: Discussionmentioning
confidence: 99%